Mental health in the “era” of artificial intelligence: technostress and the perceived impact on anxiety and depressive disorders—an SEM analysis - Lițan, Daniela-Elena (Frontiers in Psychology, 2025)
IntroductionThe aim of the current study is to analyze the relationship between mental health and the accelerated implementation and use of Artificial Intelligence (AI) in Romanian society. Given the growing integration of AI technologies, understanding their psychological impact is increasingly relevant.MethodsThe perceived impact of the changes brought by AI technology was measured using the Technostress Creators Questionnaire. Mental health, assessed in terms of anxiety and depression disorders, was measured using the Depression Anxiety Stress Scales (DASS-21R). Data were analyzed using Structural Equation Modeling (SEM).ResultsThe results supported the proposed model and confirmed both tested hypotheses, indicating that anxiety and depression symptoms are significantly associated with AI-related technostress.Discussion/ConclusionDue to the cross-sectional design, the findings should be interpreted as associative rather than causal. Nevertheless, this study provides an important contribution to the literature, addressing a notable gap in research regarding the psychological implications of AI adoption in society.